2018
DOI: 10.4054/demres.2018.39.42
|View full text |Cite
|
Sign up to set email alerts
|

Family histories and the demography of grandparenthood

Abstract: BACKGROUND Grandparenthood is an important phase of life for many individuals, and the grandparent role has consequences on younger generations and grandparents themselves. OBJECTIVE Despite the importance of the grandparent role, little is known about the demography of grandparenthood. In this study, we examine the variability of demographic aspects of grandparenthood (being a grandparent, number of grandchildren, having at least one young grandchild) according to family (partnership and fertility) histories.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The transition to grandparenthood is a time-discrete life event-the beginning of one's status as a grandparent (Luhmann et al, 2012). In terms of characteristics of major life events (Luhmann et al, 2020), the transition to grandparenthood stands out in that it is externally caused (by one's children, see also Arpino, Gumà, et al, 2018;Margolis & Verdery, 2019), but also predictable as soon as children reveal their family planning or pregnancy. The transition to grandparenthood has been labeled a countertransition due to this lack of direct control over its timing (Hagestad & Neugarten, 1985; as cited in Arpino, Gumà, et al, 2018).…”
Section: Grandparenthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…The transition to grandparenthood is a time-discrete life event-the beginning of one's status as a grandparent (Luhmann et al, 2012). In terms of characteristics of major life events (Luhmann et al, 2020), the transition to grandparenthood stands out in that it is externally caused (by one's children, see also Arpino, Gumà, et al, 2018;Margolis & Verdery, 2019), but also predictable as soon as children reveal their family planning or pregnancy. The transition to grandparenthood has been labeled a countertransition due to this lack of direct control over its timing (Hagestad & Neugarten, 1985; as cited in Arpino, Gumà, et al, 2018).…”
Section: Grandparenthoodmentioning
confidence: 99%
“…In terms of characteristics of major life events (Luhmann et al, 2020), the transition to grandparenthood stands out in that it is externally caused (by one's children, see also Arpino, Gumà, et al, 2018;Margolis & Verdery, 2019), but also predictable as soon as children reveal their family planning or pregnancy. The transition to grandparenthood has been labeled a countertransition due to this lack of direct control over its timing (Hagestad & Neugarten, 1985; as cited in Arpino, Gumà, et al, 2018). Grandparenthood is also generally positive in valence and emotionally significant if the grandparent maintains a good relationship with their child.…”
Section: Grandparenthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Their activity -actual or potentialgenerates interest in new research. The last decade has seen a rapid development of the grandparenthood demography (Arpino et al 2018;Margolis and Arpino 2019). An increasing number of grandparenthood demography studies found, inter alia, some positive psychological, social, demographic, and economic effects from grandparents' involvement in their grandchildren's lives (Arpino and Bordone 2014;Mahne and Huxhold 2015;Hilbrand et al 2017;Shubat and Shubat 2021).…”
Section: Identifying Regional Models Of Active Grandparenting In Russ...mentioning
confidence: 99%
“…Conversely, the “role strain” postulates that one’s mental health status and life satisfaction will be negatively affected when the caring obligations exceed their coping capacity [ 29 ]. Grandparenthood could be a counter-transition because it is a life change brought about by a child’s transition to parenthood [ 30 ]. Older adults tend to have little agency in deciding either the marital status of their adult children or the timing of when they will become grandparents and are sometimes required to entirely restructure their intergenerational relationships [ 31 ], which will affect their well-being on three core psychological, social, and physical fronts.…”
Section: Introductionmentioning
confidence: 99%